Newborn screening for remethylation disorders and vitamin B<Subscript>12</Subscript> deficiency-evaluation of new strategies in cohorts from Qatar and Germany - Gramer, Gwendolyn; Fang-Hoffmann, Junmin; Hoffmann, Georg F.; Okun, Jürgen G. (World journal of pediatrics, 2017)
BackgroundNewborn screening is a precondition for early diagnosis and successful treatment of remethylation disorders and classical homocystinuria (cystathionine-ß-synthase deficiency). Newborn screening for classical homocystinuria using total homocysteine measurement in dried blood spots has been very successfully performed for many years for newborns from Qatar.MethodsA new optimized newborn screening strategy for remethylation disorders and homocystinuria was developed and evaluated for newborns from Qatar using total homocysteine measurement as first-tier and methionine, methionine-phenylalanine-ratio and propionylcarnitine as second-tiers. Proposed cut-offs were also retrospectively evaluated in newborn screening samples of 12 patients with remethylation disorders and vitamin B12 deficiency from Qatar and Germany.ResultsOver a 12 months period, the proposed strategy led to a decrease in the recall rate in homocysteine screening for Qatar from 1.09% to 0.68%, while allowing for additional systematic inclusion of remethylation disorders and vitamin B12 deficiency into the screening panel for Qatar. In the evaluated period the applied strategy would have detected all patients with classical homocystinuria identified by the previous strategy and in addition 5 children with maternal nutritional vitamin B12 deficiency and one patient with an isolated remethylation disorder. Additional retrospective evaluation of newborn screening samples of 12 patients from Germany and Qatar with remethlyation disorders or vitamin B12 deficiency showed that all of these patients would have been detected by the cut-offs used in the proposed new strategy. In addition, an adapted strategy for Germany using methionine, methionine-phenylalanine-ratio and propionylcarnitine as first-tier, and homocysteine as a second-tier test was also positively evaluated retrospectively.ConclusionsThe proposed strategy for samples from Qatar allows inclusion of remethylation disorders and vitamin B12 deficiency in the screening panel, while lowering the recall rate. An adapted second-tier strategy is presented for screening in Germany and will be prospectively evaluated over the next years in a pilot project named “Newborn Screening 2020”.